Opini Publik tentang Pembangkit Listrik Tenaga Uap Suralaya (Jurnal Komunikasi Pembangunan, 2015)
Abstrak The purposes of this research: (1) to analyse public opinion about PLTU Suralaya, (2) to analyse effect of newspaper, public relations, opinion leader, and experience. This research conducting in PLTU Suralaya area, Cilegon, Banten, on January until March 2010. Population of its research is around PLTU Suralaya community. Sample of research the pain according to stratified random sampling amount 343 respondens. Collecting data conducted by observation, questioner, interview, FGD, and documentation study. Data analyses by gamma correlation with SPSS program. Public opinion influenced by opinion leader and experience. In spite of newspaper and opinion leader was not influence public opinion. Based on research result, coal ash to result in air polution among other thing to influence health, to destroy agriculture, and to durty goods. But is not man source positioning fish in the sea. Meanwhile PLTU Suralaya give positive effect in economic side, enviroment condition and is not agree that PLTU Suralaya sound to appear noises. Negative public opinion about coal ash wich influence health, to destroy agriculture, and to durty goods can be minimized by community development programm. Newspaper factor and public relations is not influence public opinion. But opinion leader and experince wich is influence public opinion. Opinion leader factor in function and message of religion figure and public figure to be able to influence to establish public opinion. Keywords: public opinion, PLTU Suralaya